2005
DOI: 10.1111/j.1365-2036.2005.02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of gastroduodenal ulcers during treatment with vascular protective doses of aspirin

Abstract: SUMMARYBackground: Aspirin is valuable for preventing vascular events, but information about ulcer frequency is necessary to inform risk-benefit decisions in individual patients. Aim: To determine ulcer prevalence and incidence in a population representative of those given aspirin therapy and evaluate risk predictors. Methods: Patients taking aspirin 75-325 mg daily were recruited from four countries. Exclusions included use of gastroprotectant drugs or other non-steroidal antiinflammatory drugs. We measured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
172
2
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(194 citation statements)
references
References 28 publications
9
172
2
11
Order By: Relevance
“…35 It has been estimated that 50 million Americans use low-dose ASA (ie, 325 mg/day or less) regularly for cardioprophylaxis. 36 The use of low-dose ASA is associated with a 2-to 4-fold increased risk of UGIE, 37,38 which is not reduced by the use of buffered or enteric-coated preparations. 39,40 Fourteen randomized placebo-controlled trials have presented data on UGIE with cardiac-dose ASA (75 to 325 mg per day) in adults.…”
Section: Gi Effects Of Asamentioning
confidence: 99%
See 1 more Smart Citation
“…35 It has been estimated that 50 million Americans use low-dose ASA (ie, 325 mg/day or less) regularly for cardioprophylaxis. 36 The use of low-dose ASA is associated with a 2-to 4-fold increased risk of UGIE, 37,38 which is not reduced by the use of buffered or enteric-coated preparations. 39,40 Fourteen randomized placebo-controlled trials have presented data on UGIE with cardiac-dose ASA (75 to 325 mg per day) in adults.…”
Section: Gi Effects Of Asamentioning
confidence: 99%
“…38,91,92 In a case-control study of 695 consecutive users of low-dose ASA with upper GI bleeding, H pylori infection was identified as an independent risk factor of upper GI bleeding (OR 4.7; 95% CI: 2.0 to 10.9). Other risk factors identified were a previous ulcer history (OR 15.2; 95% CI: 3.8 to 60.1), alcohol use (OR 4.2; 95% CI: 1.7 to 10.4), and use of calcium-channel blockers (OR 2.54; 95% CI: 1.25 to 5.14).…”
Section: Role Of H Pylorimentioning
confidence: 99%
“…The use of low doses (75-300 mg/day) versus high doses (≥500 mg), continues to prevent cancer incidence and mortality, with a more adequate toxicity profile 5,7,12,72 . In spite of the use of low-dose aspirin, the incidence of peptic ulcer disease is still 11% 73 . The risk factors associated with the development of GI bleeding would be the existence of an ulcer or previous GI bleeding, aspirin higher doses, age older than 70 years, NSAIDs and corticosteroids concomitant use and Helicobacter pylori infection 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Major GI complications are ulcers with bleeding and perforations, while minor GI complications are dyspepsia, erosions, erythema, and petechia. Yeomans et al demonstrated that, among 187 patients receiving low-dose ASA for CV disease prophylaxis, the prevalence of endoscopicallydetected GI ulcers was 11% (95% CI; 6.3 − 15.1%) 14) . Primary and secondary endpoints of numerous studies that evaluated the preventive effect of anti-ulcer agents for ASA-induced GI diseases were endoscopic evaluation, clinical outcome, and/or dyspepsia; however, these methods of evaluation have several problems.…”
Section: Introductionmentioning
confidence: 99%